Investigating Syntactic Complexity in Qatari EFL Learners’ Essays: A Mixed Methods Study - Shah, Sayyed Rashid Ali (Pakistan Languages and Humanities Review, 2024)
This mixed methods study investigates the syntactic challenges faced by EFL learners of English at the pre-intermediate level in Qatar. Employing a quantitative analysis of student essays (n=60) and qualitative interviews with students (n=15) and teachers (n=5), the study explores the prevalent errors encountered by the EFL learners, their self-perceptions of these difficulties, and the current instructional practices in Qatari classrooms. The quantitative analysis reveals verb tense and subject-verb agreement errors as the most frequent, aligning with previous research on L2 learners. While a decrease in the frequency of most errors over the semester suggests some effectiveness in the current approach, the persistence of certain errors, particularly verb tense, highlighted a need for further investigation. Qualitative data from student interviews mirrors the quantitative findings, with students reporting struggles with verb tense, subject-verb agreement, and complex sentences, and wish to have more practice materials and focused lessons. Teacher interviews show a focus on basic grammar, but limited stress on complex sentence construction. The research study recommends a need for a more nuanced method to syntactic development, explicit instruction on complex sentences and integrating grammar instruction with meaningful writing tasks. Future research can explore the effectiveness of targeted interventions to address these challenges and empower Arab learners of English to become more skillful writers.